HUBUNGAN POLA ASUH ORANG TUA DENGAN RISIKO OBESITAS PADA REMAJA DI SMK IT RAFLESIA DEPOK - Angel Sri Yuliningtias (2022)
Obesity is a condition when an individual is overweight beyond normal weight. Adolescents have a risk of obesity which may occur into adulthood that it can have a negative impact on the development of adolescents both physically and psychologically. Parental feeding management has a significant relationship with adolescent food quality. This study aims to determine the correlation between parenting patterns with the risk of obesity in adolescents at SMK IT Raflesia Depok. The method used is an observational quantitative research with analytic design and using a cross sectional study approach. The sample used was 102 samples obtained through the Stratified Random Sampling technique. Measurements were made using height and weight measurements and filling out a questionnaire using a structured instrument. The results of the analysis with the chi square test showed that there was a relationship between parenting pattern with the risk of obesity in adolescents with p value = 0.018 (<0.05). Parenting in accordance with the development of adolescence must also be considered for parents in an effort to overcome the risk of obesity.